Transforming aquaculture monitoring with real-time solutions at Salman Assalam Science Islamic Boarding School, Cirebon - Adiono, Trio; Fuada, Syifaul; Syafalni, Infall; Alfi, Feiza; Abdurrahman, Imran; Pamungkas, Sandi; Afandi, Najma Khansa Alya; Hasugian, Leonardi Paris (Community Empowerment, 2024)
The aim of this activity is to disseminate real-time, 24-hour aquaculture water monitoring devices remotely at the Salman Assalam Science Islamic Boarding School in Cirebon, West Java. The Salman Assalam Science Islamic Boarding School manages various types of tilapia, catfish, and pomfret cultivation ponds used to support the economy and fulfill the food needs of the students. The activities include planning, implementation, and evaluation. The results of this activity include the development of a laboratory-level device, comprising a buoy, solar panels, and electronic modules with several types of electronic sensors. The device is equipped with a dashboard to observe real-time measurements in fish ponds, including parameters such as water temperature, dissolved oxygen, turbidity, pH, air temperature, humidity, battery voltage, total dissolved density, and solar cell voltage. Data is presented in the form of graphs and tables accessible via a web browser, allowing partners to access it from laptops or smartphones.